Morning glory syndrome: a histopathological study. - Manschot, W A (1990)
The clinical and histopathological findings in a case of morning glory syndrome are described. Axial optic nerve retrodisplacement into a peripapillary scleral ectasia (staphyloma), absence of fibrous lamina cribrosa, and optic nerve atrophy were associated with various other, non-inherent ocular developmental anomalies. The uninterrupted lining of the inner wall of the staphyloma by one-layered, normal retinal pigment epithelium proves that the syndrome is not due to a neuroectodermal closure defect.